2022
DOI: 10.3390/ani12202880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eugenol on Water Quality and the Metabolism and Antioxidant Capacity of Juvenile Greater Amberjack (Seriola dumerili) under Simulated Transport Conditions

Abstract: This study investigated the effects of added eugenol on water quality and the metabolism and antioxidant capacity of the liver and gills of the greater amberjack (Seriola dumerili) during simulated transport. The juvenile fish (10.34 ± 1.33 g) were transported in sealed plastic bags containing different eugenol concentrations at a density of 24.79 kg/m3 for 8 h. The different eugenol concentrations were divided into five groups: 0 μL/mL (control group), 0.0125 μL/mL, 0.025 μL/mL, 0.0375 μL/mL, and 0.05 μL/mL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Otherwise, the highest concentration of clove oil (0.2mL/L of water) significantly (p<0.05) has a shorter time to anesthesia the payangka fish. Clove oil contains eugenol compounds which have antioxidant, antifungal, analgesic, and antiseptic activities (He et al, 2022). In general, clove oil was an efficient anesthetic at low concentrations (Fernandez et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the highest concentration of clove oil (0.2mL/L of water) significantly (p<0.05) has a shorter time to anesthesia the payangka fish. Clove oil contains eugenol compounds which have antioxidant, antifungal, analgesic, and antiseptic activities (He et al, 2022). In general, clove oil was an efficient anesthetic at low concentrations (Fernandez et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, research conducted by Bahi et al, (2018) showed that administration of clove oil on gilthead seabream did not affect glucose levels. According to He et al, (2022), eugenol could reduce the metabolic capacity of fish, which is shown by reducing glucose concentration. Our recent study showed that the high concentration of clove oil and the length of time of immersing can increase plasma glucose.…”
Section: Resultsmentioning
confidence: 99%